2022
DOI: 10.1111/ijfs.16057
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel with the network structure fabricated by anthocyanin–gelatin crosslinking and improved mineral encapsulation ability

Abstract: Summary In this study, four polyphenols (tea polyphenol, procyanidin, anthocyanin and gallic acid) were applied to crosslink with gelatin (G), in order to explore the crosslinking mechanisms of polyphenol–gelatin hydrogels with desirable properties and its potential applications. The results showed that the crosslinking effect of polyphenols with gelatin was affected by pH and the types and concentration of polyphenols. The network of polyphenol–gelatin on the microscopic level was ordered with 0.075% polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…13 Although the incorporation of GA can endow a hydrogel system with better mechanical strength and energy dissipation capabilities, importantly, when the concentration ratio of GA to polymer exceeds a certain threshold, the resulting excessive and uneven polymerization can lead to increased brittleness of the gel network system. 54,82 For instance, with increasing GA and Zn 2+ contents, the elastic modulus and toughness of PVA/ PAM/GA-Zn 2+ hydrogels increased first and then decreased. 80 In hydrogels formed by GA and proteins, excess polyphenols aggregate with proteins, thereby impacting gelation.…”
Section: Improved Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although the incorporation of GA can endow a hydrogel system with better mechanical strength and energy dissipation capabilities, importantly, when the concentration ratio of GA to polymer exceeds a certain threshold, the resulting excessive and uneven polymerization can lead to increased brittleness of the gel network system. 54,82 For instance, with increasing GA and Zn 2+ contents, the elastic modulus and toughness of PVA/ PAM/GA-Zn 2+ hydrogels increased first and then decreased. 80 In hydrogels formed by GA and proteins, excess polyphenols aggregate with proteins, thereby impacting gelation.…”
Section: Improved Mechanical Propertiesmentioning
confidence: 99%
“…They found that the formation of the hydrogel is closely related to the concentration of GA and the pH. Studies have indicated that at a pH of 8 and a polyphenol concentration of 0.075%, 82 the hydrogel network is most stable. Additionally, another study showed that GA-gelatin hydrogels can promote the proliferation of dental pulp stem cells, demonstrating their potential application in tissue regeneration.…”
Section: Ga-containing Hydrogelsmentioning
confidence: 99%
“…Gelatin (Ge) is a biocompatible, biodegradable polymer that can be obtained by partial hydrolysis of collagen (Chen et al ., 2022), which can be dissolved in water under appropriate circumstances to form a solution with different viscosity. The natural attributes, edibility, low cost, rich sources, safety, and environmentally friendly characteristics (Rather et al ., 2022) could make gelatin‐based products an ideal carrier or stabiliser for many bioactive compounds (Usman et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%